2010
DOI: 10.1021/ma1002084
|View full text |Cite
|
Sign up to set email alerts
|

Shear Deformation and Ferroelectricity in Chiral SmC* Main-chain Elastomers

Abstract: Ferroelectric smectic main-chain liquid crystalline elastomers were synthesized and subjected to simple shear deformation to achieve reorientation of the layer structure and the formation of a macroscopic spontaneous polarization. The phase behavior and structural parameters of these elastomers are investigated and discussed. A shear-induced splitting of the X-ray scattering intensity distribution is found. A splitting of the sample in domains of two director orientations that couple differently to the shear d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 34 publications
(90 reference statements)
1
25
0
Order By: Relevance
“…Sánchez-Ferrer et al [64] reported the polydomain to monodomain (P-M) transition caused by uniaxial strain in these materials. The monodomain obtained is termed as pseudo-monodomain [68] because of the conical distribution of the layers around the mechanically induced director. Application of shear deformation perpendicular to the director [61] rendered a perfectly monodomain sample from the pseudo-mono-domain state.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
“…Sánchez-Ferrer et al [64] reported the polydomain to monodomain (P-M) transition caused by uniaxial strain in these materials. The monodomain obtained is termed as pseudo-monodomain [68] because of the conical distribution of the layers around the mechanically induced director. Application of shear deformation perpendicular to the director [61] rendered a perfectly monodomain sample from the pseudo-mono-domain state.…”
Section: Polydomain Smectic-c Main Chain Liquid Crystal Elastomersmentioning
confidence: 99%
“…Bent core LCEs have been developed to produce giant flexoelectricity for microscale parasitic power generation [38,39]. Toward this end, main-chain ferroelectric smectic LCEs were synthesized, with analysis of shear deformation and ferroelectricity [40]. However, strong electric fields are necessary to produce actuation in ferroelectric LCEs, and the amplitudes of the resulting mechanical contractions are quite small [35].…”
Section: Open Accessmentioning
confidence: 99%
“…These materials show both the direct piezoelectric effect in pseudo-monodomains [29], as well as the inverse piezoelectric effect [30]. Spontaneous polarization of pseudomonodomains has also been reported [22].…”
Section: Introductionmentioning
confidence: 87%
“…We will refer to this as a pseudo-monodomain [see Fig. 1(b)] [22] in order to distinguish it from a monodomain, which has both the layer normal and the director uniformly aligned, and a polydomain, which has random director and layer normal alignment. The layer normals in the pseudo-monodomain can be aligned by a second uniaxial deformation perpendicular to one of the layer normals [23], or alternatively by a shear deformation perpendicular to the director [24].…”
Section: Introductionmentioning
confidence: 99%